2018
DOI: 10.1186/s12957-018-1342-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of kinesin KIF18A in the invasion and metastasis of hepatocellular carcinoma

Abstract: BackgroundKIF18A is associated with a variety of tumours; however, the specific mechanism of action of KIF18A in hepatocellular carcinoma (HCC) remains unclear. In this study, in vitro and in vivo experiments were performed with the aim of exploring the potential function and molecular mechanism of kinesin KIF18A in the occurrence and development of HCC.MethodsWe detected the expression of KIF18A in tumour and adjacent tissues as well as cell proliferation, cell invasion and migration in hepatoma cells after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Previous studies revealed that knockdown of KIF18A expression in human breast carcinoma cells caused increase of G2/M populations when compared with control RNAi cells . Recent study has also confirmed that the expression of cell cycle‐related protein such as cyclin B1 was decreased after knockdown of KIF18A in hepatocellular carcinoma . KIF18A might promote the malignant behavior, including proliferation, invasion, and metastasis by promoting cell cycle signaling pathways.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies revealed that knockdown of KIF18A expression in human breast carcinoma cells caused increase of G2/M populations when compared with control RNAi cells . Recent study has also confirmed that the expression of cell cycle‐related protein such as cyclin B1 was decreased after knockdown of KIF18A in hepatocellular carcinoma . KIF18A might promote the malignant behavior, including proliferation, invasion, and metastasis by promoting cell cycle signaling pathways.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, a large number of sample information analysis based on multiple data sets showed that KIF18A expression was increased in a variety of tumor tissues [13,15,[35][36][37] (Figure 1a), and the expression of KIF18A mRNA ( Figure 1b) and protein ( Figure 7) in glioma was signi cantly increased. Therefore, KIF18A expression was increased in gliomas, and its relationship with glioma and its function were further veri ed.…”
Section: Discussionmentioning
confidence: 62%
“…Notably, some recent reports suggest that KIF18A are also involved in the process of multiple tumors. Kif18A is associated with the occurrence and development of liver cancer [13], breast cancer [14], ovarian cancer [15] and can be used as potential biomarkers for breast cancer [16], colorectal [17] and hepatocellular carcinoma [18]. In contrast, the expression of kif18a is low in gastric cancer, which is associated with poor prognosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was reported that Kif18a influences mouse germ cell proliferation (Czechanski et al, 2015;Luo et al, 2018;Zhong et al, 2019), we first investigated such potential effect of human KIF18A on TCam-2 cells, which originates from male germ cells. For that purpose we performed MTS proliferation assay upon KIF18A knockdown, starting at 24 h up to 120 h post transfection.…”
Section: Knockdown Of Kif18a Caused Decreased Tcam-2 Cell Proliferatimentioning
confidence: 99%